The Influence of bFGF on the Fabrication of Microencapsulated Cartilage Cells under Different Shaking Modes - Zhou, Xia (Polymers (Basel), 2019)
Cell encapsulation in hydrogels has been extensively used in cytotherapy, regenerative medicine, 3D cell culture, and tissue engineering. Herein, we fabricated microencapsulated cells through microcapsules loaded with C5.18 chondrocytes alginate/chitosan prepared by a high-voltage electrostatic method. Under optimized conditions, microencapsulated cells presented uniform size distribution, good sphericity, and a smooth surface with different cell densities. The particle size distribution was determined at 150–280 μm, with an average particle diameter of 220 μm. The microencapsulated cells were cultured under static, shaking, and 3D micro-gravity conditions with or without bFGF (basic fibroblast growth factor) treatment. The quantified detection (cell proliferation detection and glycosaminoglycan (GAG)/type II collagen (Col-II)) content was respectively determined by cell counting kit-8 assay (CCK-8) and dimethylmethylene blue (DMB)/Col-II secretion determination) and qualitative detection (acridine orange/ethidium bromide, hematoxylin-eosin, alcian blue, safranin-O, and immunohistochemistry staining) of these microencapsulated cells were evaluated. Results showed that microencapsulated C5.18 cells under three-dimensional microgravity conditions promoted cells to form large cell aggregates within 20 days by using bFGF, which provided the possibility for cartilage tissue constructs in vitro. It could be found from the cell viability (cell proliferation) and synthesis (content of GAG and Col-II) results that microencapsulated cells had a better cell proliferation under 3D micro-gravity conditions using bFGF than under 2D conditions (including static and shaking conditions). We anticipate that these results will be a benefit for the design and construction of cartilage regeneration in future tissue engineering applications.